Introducing wearable haptics for rendering velocity feedback in VR serious games for neuro-rehabilitation of children - Camardella, Cristian; Chiaradia, Domenico; Bortone, Ilaria; Frisoli, Antonio; Leonardis, Daniele (Frontiers in Virtual Reality, 2023)
Rehabilitation in virtual reality offers advantages in terms of flexibility and parametrization of exercises, repeatability, and continuous data recording and analysis of the progress of the patient, also promoting high engagement and cognitive challenges. Still, most of the proposed virtual settings provide a high quality, immersive visual and audio feedback, without involving the sense of touch. In this paper, we show the design, implementation, and first evaluation of a gaming scenario for upper limb rehabilitation of children with cerebral palsy. In particular, we took care to introduce haptic feedback as a useful source of sensory information for the proposed task, considering—at the same time—the strict constraints for haptic wearable devices to comply with patient’s comfort, residual motor abilities, and with the embedded tracking features of the latest VR technologies. To show the potential of haptics in a rehabilitation setup, the proposed device and rendering method have been used to improve the velocity control of upper limb movements during the VR exercise, given its importance as a motor recovery metric. Eight healthy participants were enrolled, and results showed that haptic feedback can lead to lower speed tracking errors and higher movement smoothness, making the proposed setup suitable to be used in a rehabilitation context as a way to promote movement fluidity during exercises.